Inter-observer variation in delineating the coronary arteries as organs at risk. Issue 1 (January 2017) - Wennstig, Anna-Karin; Garmo, Hans; Hållström, Per; Nyström, Petra Witt; Edlund, Per; Blomqvist, Carl; Sund, Malin; Nilsson, Greger
Abstract: Purpose: To determine the inter-observer variation in delineating the coronary arteries as organs at risk (OAR) in breast cancer (BC) radiotherapy (RT) and how this variation affects the estimated coronary artery radiation dose. Method: Delineation of the left main and the left anterior descending coronary artery (LMCA and LAD), and the right coronary artery (RCA), by using the heart atlas by Feng et al., was performed by three radiation oncologists in 32 women who had received adjuvant RT for BC. Centres of the arteries were calculated and distances between artery centres were measured and the artery radiation doses were estimated. The intraclass correlation coefficient (ICC) was used to quantify the variability in doses. Results: Along the extent of RCA, the median distance between centres of arteries varied from 2 to 9 mm with similar patterns over pairs of oncologists. For the LMCA-LAD the median distance varied from 1 to 4 mm. The estimated maximum radiation doses showed an ICC variation from 0.82 to 0.97. Conclusion: The coronary arteries can be reliably identified and delineated as OARs in BC RT. The spatial variance is limited and the total variation in radiation dose is almost completely determined by the between patient variation.